Vibration analysis of paper machine's asymmetric tube roll supported by spherical roller bearings. (1st May 2018) - Heikkinen, Janne E.; Ghalamchi, Behnam; Viitala, Raine; Sopanen, Jussi; Juhanko, Jari; Mikkola, Aki; Kuosmanen, Petri
Highlights: Asymmetric beam elements are used to study vibrations of a paper machine tube roll. Asymmetric structural properties and bearing inaccuracies may result in vibrations. Bearing waviness contribute mostly to subcritical vibrations. Asymmetric beam model is able to capture 2X responses due to gravity. Abstract: This paper presents a simulation method that is used to study subcritical vibrations of a tube roll in a paper machine. This study employs asymmetric 3D beam elements based on the Timoshenko beam theory. An asymmetric beam model accounts for varying stiffness and mass distributions. Additionally, a detailed rolling element bearing model defines the excitations arising from the set of spherical roller bearings at both ends of the rotor. The results obtained from the simulation model are compared against the results from the measurements. The results indicate that the waviness of the bearing rolling surfaces contributes significantly to the subcritical vibrations while the asymmetric properties of the tube roll have only a fractional effect on the studied vibrations.